Intraocular Pressure Changes During Valsalva Manoeuvre in Young and Middle-Aged Adult Populations - Firdaus Yusof; Huzaifah Abdul Hamid; Noor Azian Hamdan; Raja Fatihah Raja Bidin; Nur Raihan Esa; Aida Hazira Ruslan; Syazwan Hafiz Mohd (International Journal of Allied Health Sciences, 2025)
Background: Intraocular pressure (IOP) is a critical physiological parameter that maintains the structural integrity and function of the eye. Understanding its dynamic behaviour under transient physiological stressors is essential for comprehensive ocular assessment. The Valsalva manoeuvre (VM) acutely increases central and episcleral venous pressures, providing a natural model for studying short-term IOP fluctuations. This study aimed to investigate and compare dynamic IOP changes during the VM between young and middle-aged adults to establish age-specific response patterns. Methods: A cross-sectional study was conducted among 42 healthy participants, equally divided into a young adult group (18–25 years) and a middle-aged adult group (40–65 years). IOP was recorded at four time points: pre-VM (0 s), intra-VM (10 s and 20 s) and post-VM (900 s). The VM was standardized by maintaining an expiratory pressure of 40 mmHg for 20 seconds using an aneroid manometer. Repeated-measures ANOVA with Bonferroni-corrected paired t-tests assessed IOP changes within each group, while independent-samples t-tests compared responses between age groups. Results: Both age groups exhibited a significant transient IOP elevation, peaking at 10 s during the VM before declining toward baseline. In young adults, mean IOP increased from 14.48 ± 3.34 mmHg (pre-VM) to 18.05 ± 3.53 mmHg (10 s), while in middle-aged adults, it rose from 14.00 ± 3.05 mmHg to 17.81 ± 3.06 mmHg (10 s). By 900 s post-VM, IOP had returned to near-baseline levels in both groups. No statistically significant inter-group difference in IOP change was found across any VM phase (p > 0.05). Conclusion: The transient IOP elevation observed in both groups reflects the physiological mechanism in which the VM raises episcleral venous pressure, temporarily impeding aqueous humour outflow. The rapid recovery of IOP to baseline indicates effective ocular and systemic autoregulation following acute venous congestion. The absence of a significant age-related difference suggests that hemodynamic defence and ocular pressure regulatory mechanisms remain comparably efficient between young and middle-aged adults.